Teachers' Readiness in Inserting the 21st Century Skills in the Lesson Plan in Teaching English - Ni Luh Ratih Luciana; Ni Nyoman Padmadewi; Luh Putu Artini; Luh Gd Rahayu Budiarta (Universitas Pendidikan Ganesha, 2020)
The 21st-century learning outcomes are essential to be achieved by the students nowadays. A lesson plan is one of the mediums used to insert the skills of the 21st century, which needed to be improved by the students. This study examined English teachers’ readiness in inserting the 21st-century skills in planning the lesson in the city area and suburb area of Badung Regency. This study belonged to a case study and was conducted using a sequential embedded mixed-method, in which mixed the quantitative results with qualitative results to get more valid data. A questionnaire consisted of 17 items used to know the readiness of English teachers, combined with the results on document analysis. Based on the results of the investigation, it showed inconsistent answers of English teachers in the city area and suburb area based on the results on questionnaire and document analysis. English teachers perceived they were ready to insert the 21st-century skills but, based on results on document analysis, it showed English teachers mostly added learning and innovation skills and information, media, and technology skills in the lesson plan. It is suggested English teachers should be more ready by looking up at the standardization of the 21st-century education then combined it with attending seminars on related topics about the implementation of the 21st-century skills.